2022
DOI: 10.3390/foods11172700
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Auricularia auricula Polysaccharides on Gut Microbiota and Metabolic Phenotype in Mice

Abstract: Personalized diets change the internal metabolism of organisms, which, in turn, affects the health of the body; this study was performed to explore the regulatory effects of polysaccharides extracted from Auricularia auricula on the overall metabolism and gut microbiota in normal C57BL/6J mice. The study was conducted using metabolomic and microbiomic methods to provide a scientific basis for further development and use of Auricularia auricula resources in the Qinba Mountains and in nutritional food with Auric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Polysaccharides from Grifola frondose and Lentinula edodes significantly increased the abundance of Alistipes in mice [ 156 , 157 ]. Auricularia auricula polysaccharides markedly increased the level of Bifidobacterium animalis, Morchella esculenta, and Inonotus obliquus polysaccharides enhanced the level of Lactobacillus in mice [ 77 , 158 , 159 ].…”
Section: Mechanism Of the Anti-diabetic Effects Of Polysaccharides Th...mentioning
confidence: 99%
“…Polysaccharides from Grifola frondose and Lentinula edodes significantly increased the abundance of Alistipes in mice [ 156 , 157 ]. Auricularia auricula polysaccharides markedly increased the level of Bifidobacterium animalis, Morchella esculenta, and Inonotus obliquus polysaccharides enhanced the level of Lactobacillus in mice [ 77 , 158 , 159 ].…”
Section: Mechanism Of the Anti-diabetic Effects Of Polysaccharides Th...mentioning
confidence: 99%
“…According to the research, as shown in Figure 5 , there are as many as 51 metabolites regulated by Auricularia auricula polysaccharide, which are mainly concentrated in the arginine biosynthesis pathway, followed by the arginine and proline, glycine, serine, and threonine, glycerophospholipids, and sphingolipid metabolic pathways [ 60 ]. These pathways can lower total and LDL cholesterol levels and alter the composition of the intestinal flora.…”
Section: Physiological Activity and Product Development Of Polysaccha...mentioning
confidence: 99%
“…The fruit bodies of Auricularia auricula are rich in polysaccharides and have been historically used both as a food and as a drug in oriental countries for over 1000 years [17] . The most functional components of Auricularia auricula are considered to be the polysaccharides, which have been suggested to play important biological roles, such as antioxidant, hypoglycemic, hypolipidemic, immunomodulatory, antitumor and antiviral activities [18] , [19] , [20] , [21] , [22] , [23] , [24] . However, whether Auricularia auricula polysaccharides (AAP) provide direct influence over bodyweight and obesity-linked metabolic disorders remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%